The ontogenesis of narrative: from moving to meaning - Delafield-Butt, Jonathan T.; Trevarthen, Colwyn (Frontiers in Psychology, 2015)
Narrative, the creation of imaginative projects and experiences displayed in expressions of movement and voice, is how human cooperative understanding grows. Human understanding places the character and qualities of objects and events of interest within stories that portray intentions, feelings, and ambitions, and how one cares about them. Understanding the development of narrative is therefore essential for understanding the development of human intelligence, but its early origins are obscure. We identify the origins of narrative in the innate sensorimotor intelligence of a hypermobile human body and trace the ontogenesis of narrative form from its earliest expression in movement. Intelligent planning, with self-awareness, is evident in the gestures and motor expressions of the mid-gestation foetus. After birth, single intentions become serially organised into projects with increasingly ambitious distal goals and social meaning. The infant imitates others’ actions in shared tasks, learns conventional cultural practices, and adapts his own inventions, then names topics of interest. Through every stage, in simple intentions of foetal movement, in social imitations of the neonate, in early proto-conversations and collaborative play of infants and talk of children and adults, the narrative form of creative agency with it four-part structure of ‘introduction’, ‘development’, ‘climax’ and ‘resolution’ is present. We conclude that shared rituals of culture and practical techniques develop from a fundamental psycho-motor structure with its basic, vital impulses for action and generative process of thought-in-action that express an integrated, imaginative and sociable Self. This basic structure is evident before birth and invariant in form throughout life. Serial organisation of single, non-verbal actions into complex projects of expressive and explorative sense-making become conventional meanings and explanations with propositional narrative power.